Representation of Toxic Masculinity in Itisha Nagar’s Speech: A Critical Discourse Analysis - Mutiara Ulil Zanna; Suprayogi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examines how toxic masculinity is constructed & contested in Itisha Nagar’s TEDx Talk, “From ‘Man’ to ‘(Hu)man)”. Employing Van Dijk’s Critical Discourse Analysis (CDA) framework, the research analyzes the transcript across three levels: macrostructure, superstructure, and microstructure. At the macrostructural level, the talk frames toxic masculinity as a systemic cultural problem rather than an individual flaw. The superstructure reveals how the speech is organized to contrast traditional and progressive views of masculinity. The microstructure highlights the ideological weight of linguistic choices such as pronouns, verbs, and evaluative adjectives. The dataset consists of a transcript of 2,102 words from a 13:34-minute talk available on the official TED YouTube channel. The findings demonstrate that Nagar frequently employs exclusion pronouns (e.g., they, them, their) to expose societal groups that reinforce toxic masculine norms, while simultaneously reframing masculinity through inclusive perspectives. Overall, the study shows how public discourse operates as a site of ideological negotiation, deconstructing patriarchal values and promoting models of masculinity grounded in empathy, equality, and shared humanity.